2002
DOI: 10.2320/matertrans.43.2673
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Improvement of NdFeB Magnetic Powders by the Zn Vapor Sorption Treatment

Abstract: The microstructural modification for NdFeB magnetic powders (MQP-B) after Zn vapor sorption has been investigated by transmission electron microscopy (TEM). It is found that a coating layer about 100 nm thick was formed on the surface of powder. Selected area electron diffraction (SAED) pattern and high resolution transmission electron microscopy (HRTEM) analyses show that the coating layer consists of condensed nano-scale crystallites of Fe 11 Zn 40 , NdZn 5 and Zn. After the temperature for Zn vapor sorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The observation on the corroded microstructures of HDDR-NdFeB powders shows that the altered layer covers the surface and the wetting layer is formed along the Nd 2 (Fe,Co) 14 (Figs. 2 and 3).…”
Section: Mechanism Of Corrosion and Magnetic Propertymentioning
confidence: 96%
See 4 more Smart Citations
“…The observation on the corroded microstructures of HDDR-NdFeB powders shows that the altered layer covers the surface and the wetting layer is formed along the Nd 2 (Fe,Co) 14 (Figs. 2 and 3).…”
Section: Mechanism Of Corrosion and Magnetic Propertymentioning
confidence: 96%
“…Co 11.5 B 6.0 Zr 0.1 (at%), and reported that the powders are made of homogeneous Nd 2 (Fe,Co) 14 B grains about 300 nm in diameter with clean boundaries. This would be that the Nd composition of the HDDR-NdFeB powders is closer to the stoichiometry of Nd 2 (Fe,-Co) 14 B. HDDR-NdFeB powders with such a microstructure are suitable for the production of the bonded magnets with high magnetic properties, because the size of Nd 2 (Fe,Co) 14 B grains near to the critical single magnetic domain size leads to high coercivity. The present alloy contains a higher Co content and a small amount of Ga in order to increase the Curie temperature and the magnetic anisotropy.…”
Section: Microstructure Before Exposure Experimentsmentioning
confidence: 96%
See 3 more Smart Citations